Impact of Hospitalization on Sarcopenia, NADPH-Oxidase 2, Oxidative Stress, and Low-Grade Endotoxemia in Elderly Patients - Chiara Bagnato; Arianna Magna; Elena Mereu; Sciaila Bernardini; Simona Bartimoccia; Roberta Marti; Pietro Enea Lazzerini; Alessandra D’Amico; Evaristo Ettorre; Giovambattista Desideri; Pasquale Pignatelli; Francesco Violi; et al. (Antioxidants)
Background: Hospitalization in older adults often worsens sarcopenia due to prolonged bed rest, poor nutrition, and inactivity. This study examined how hospitalization impacts muscle mass, focusing on oxidative stress and gut-derived endotoxemia. Methods: Thirty-one hospitalized older adults were compared with 31 outpatients. Ultrasound was used to measure the thickness of the rectus femoris (RF), intercostal, and diaphragmatic muscles at admission and discharge. Serum levels of LPS, zonulin, sNOX2-dp, and H2O2 were also assessed. Results: Hospitalized patients had higher serum levels of sNOX2-dp, H2O2, LPS, and zonulin than outpatients. In hospitalized patients, significant increases were observed at discharge compared to admission levels in sNOX2-dp (20.9 ± 6.5 to 23.8 ± 7.5 pg/mL; p = 0.004), H2O2 (24.4 ± 9.8 to 32.8 ± 14.5 µM; p = 0.01), LPS (30.4 ± 12.6 to 43.3 ± 16.35 pg/mL; p < 0.001), and zonulin (2.06 ± 1.23 to 2.95 ± 1.33 ng/mL; p < 0.001). Ultrasound data revealed a reduction in RF muscle thickness (−35%) (0.58 ± 0.29 to 0.38 ± 0.31 cm, p < 0.001), intercostal muscle thickness (−28%) (0.22 ± 0.08 to 0.16 ± 0.06 cm, p < 0.001), and diaphragmatic muscle thickness (−26%) (0.19 ± 0.06 to 0.14 ± 0.04 cm, p < 0.001) at discharge compared to admission. Additionally, muscle strength, measured using the hand-grip test, showed a 25% reduction. Regression analysis revealed correlations between RF muscle loss and increases in sNOX2-dp and H2O2, as well as between NOX2, H2O2, and LPS with zonulin. Conclusions: Hospitalization in older adult patients elevates NOX2 blood levels, correlating with reduced muscle mass. Increased low-grade endotoxemia may trigger NOX2 activation, generating oxidative stress that accelerates muscle degeneration and can lead to sarcopenia.